Monocytes and Monocyte-Derived Antigen-Presenting Cells Have Distinct Gene Signatures in Experimental Model of Multiple Sclerosis - Monaghan, Kelly L.; Zheng, Wen; Hu, Gangqing; Wan, Edwin C. K. (Frontiers in Immunology, 2019)
Multiple sclerosis (MS) is a chronic inflammatory disease mediated by a complex interaction between the autoreactive lymphocytes and the effector myeloid cells within the central nervous system (CNS). In a murine model of MS, experimental autoimmune encephalomyelitis (EAE), Ly6Chi monocytes migrate into the CNS and further differentiate into antigen-presenting cells (APCs) during disease progression. Currently, there is no information about gene signatures that can distinguish between monocytes and the monocyte-derived APCs. We developed a surface marker-based strategy to distinguish between these two cell types during the stage of EAE when the clinical symptoms were most severe, and performed transcriptome analysis to compare their gene expression. We report here that the inflammatory CNS environment substantially alters gene expression of monocytes, compared to the monocyte differentiation process within CNS. Monocytes in the CNS express genes that encode proinflammatory cytokines and chemokines, and their expression is mostly maintained when the cells differentiate. Moreover, monocyte-derived APCs express surface markers associated with both dendritic cells and macrophages, and have a significant up-regulation of genes that are critical for antigen presentation. Furthermore, we found that Ccl17, Ccl22, and Ccr7 are expressed in monocyte-derived APCs but not the Ly6Chi monocytes. These findings may shed light on identifying molecular signals that control monocyte differentiation and functions during EAE.